GINKGOPHYTES FROM THE UPPER PERMIAN OF THE BLETTERBACH GORGE (NORTHERN ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
Fossil evidence of late Palaeozoic ginkgophytes is rare; Palaeozoic floras in which ginkgophytes are abundant or represent a predominant element have not previously been described. The late Permian (Lopingian) flora from the Gröden/Val Gardena Sandstone of the Bletterbach gorge in the Dolomites (northern Italy) contains an unusually large proportion of ginkgophytes. The fossils include the foliage taxa Baiera digitata and Sphenobaiera sp., as well as putative O-ha-tsuki -type fertile leaves, seeds, and several ginkgophyte-like leaf types of uncertain affinities. Local mass occurrences of ginkgophyte leaves have also been observed.The Bletterbach flora suggests that ginkgophytes were important elements in certain vegetation types (probably forests) as early as the late Permian.